Research on the Development of Art and Rural Culture Revitalization from the Perspective of New Media Communication - Fang Yong; Liang Jianhui (MATEC Web of Conferences, 2022)
New Media is the witness of rural culture revitalization, and also an important force to promote rural culture revitalization. With the development and application of new media becoming more and more mature, it will be on the basis of enriching rural cultural life in an all-round way by giving full play to the advantages of new media carrier and communication, and promoting the deep integration of the revitalization of art and rural culture, keep the vitality of artistic creation, and consolidate the ideological foundation of rural revitalization. Based on the study of new media communication, this paper systematically discusses the development value and implementation strategy of art and rural culture revitalization and integration.